2017
DOI: 10.1371/journal.pgen.1007016
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of parallel adaptation at two timescales in Drosophila

Abstract: Two interesting unanswered questions are the extent to which both the broad patterns and genetic details of adaptive divergence are repeatable across species, and the timescales over which parallel adaptation may be observed. Drosophila melanogaster is a key model system for population and evolutionary genomics. Findings from genetics and genomics suggest that recent adaptation to latitudinal environmental variation (on the timescale of hundreds or thousands of years) associated with Out-of-Africa colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 113 publications
0
24
0
Order By: Relevance
“…First, a high level of genetic diversity in the species provides substantial standing genetic variation and potentially beneficial mutations. Similarly, Zhao et al [49] showed that the more genetically diverse species Drosophila hydei contained more adaptive alleles than D. melanogaster. Second, the recent timing of expansion and divergence in maize has likely affected the extent of parallelism.…”
Section: Discussionmentioning
confidence: 95%
“…First, a high level of genetic diversity in the species provides substantial standing genetic variation and potentially beneficial mutations. Similarly, Zhao et al [49] showed that the more genetically diverse species Drosophila hydei contained more adaptive alleles than D. melanogaster. Second, the recent timing of expansion and divergence in maize has likely affected the extent of parallelism.…”
Section: Discussionmentioning
confidence: 95%
“…In recognition of this, a second widely adopted approach is to generate an empirical distribution of a given summary statistic and to compare individual loci to the genome-wide distribution under the assumption that loci subject to selection will be outliers [e.g. 78 84 ]. The rationale for this approach is that the demographic history of the population will shape patterns of variation genome-wide, so that the distribution of variation across loci will reflect the demographic history even if the actual history is unknown.…”
Section: Methodsmentioning
confidence: 99%
“…The recent development of genomics has allowed identification of clinal genomic variants, which are candidates for thermal adaptation (e.g., Kolaczkowski et al 2011; Fabian et al 2012; Bozicevic et al 2016; Mateo et al 2018). There is also evidence of parallel evolution at the genomic and transcriptomic level (Reinhardt et al 2014; Bergland et al 2015; Machado et al 2015; Zhao et al 2015; Juneja et al 2016; Zhao and Begun 2017). Some of these studies compared clines between species (which may have somewhat distinct biology), while others compared clines between Australia and North America (which both feature primarily European ancestry with clinally variable African admixture).…”
Section: Introductionmentioning
confidence: 99%